Design of a TCM System Based on Vibration Signal for Metal Turning Processes. (2015) - González-Laguna, A.; Barreiro, J.; Fernández-Abia, A.; Alegre, E.; González-Castro, V.
Abstract: This paper presents a study about the identification of cutting tool wear state by means of vibration signal analysis in steel dry turning operations. Analyzing the RMS value evolution and FFT frequency spectra of signal an on-line tool condition monitoring system has been developed. The main purpose is to determine the instant from which tool condition is considered unacceptable affecting machining process quality. After the analysis was carried out, the main conclusion is that both the RMS and frequency amplitude ranges of certain spectrum bands are related to tool wear.